2018
DOI: 10.1016/j.agee.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mowing, grazing and fertilization on soil seed banks in temperate grasslands in Central Europe

Abstract: Highlights (max 85 characters incl. spaces per point)-Grassland management has complex, direct and indirect effects on soil seed banks-Grazing increased species richness of soil seed banks-Mowing and fertilization decreased species richness and seedling density-Seed banks are indirectly influenced by factors shaping the aboveground vegetation-Grazed grasslands might be more resilient towards soil disturbances than mown ones

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 42 publications
(69 reference statements)
1
31
0
Order By: Relevance
“…One study within our analysis observed grazing to promote seed dispersal of target species (Baasch et al, 2016). Grazers play an important role in the continuous removal of leaf litter and generate space for new recruitment (Lengyel et al, 2012; Török et al, 2018), which can promote species richness (Klaus et al, 2018; Towne, Hartnett, & Cochran, 2005). Germination of the native North American prairie grass, Nassella pulchra was enhanced by burning and sheep grazing (Dyer, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study within our analysis observed grazing to promote seed dispersal of target species (Baasch et al, 2016). Grazers play an important role in the continuous removal of leaf litter and generate space for new recruitment (Lengyel et al, 2012; Török et al, 2018), which can promote species richness (Klaus et al, 2018; Towne, Hartnett, & Cochran, 2005). Germination of the native North American prairie grass, Nassella pulchra was enhanced by burning and sheep grazing (Dyer, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Forb cover was also observed to increase in Prairie grasslands when exposed to grazing from cattle and bison (Towne et al, 2005). Therefore, grazing intensities should be carefully managed to suit a particular system, particularly during drought periods to promote competition from native perennial grasses (Klaus et al, 2018), and resting paddocks from grazing when natives are emerging, particularly if herbage is sparse, could improve their establishment and survival (Clarke & Davison, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Seeds in soil seed banks are composed of the legacies of past vegetation, the present standing species and the dispersed seeds from adjacent communities. Thus, land use history, landscape traits, management regimes, disturbance intensity, standing vegetation type, and seed traits are all potential factors that influence the soil seed bank species composition and density (Bossuyt & Hermy 2001; Andreasen et al 2018; Klaus et al 2018). Seed size generally can influence seed longevity, seed predation, seed dispersal, and the number of seeds that can be produced with a given amount of energy (Gómez 2004; Moles & Westoby 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we found that grazing management increased the number of species in the seed bank and tended to homogenise the species composition between restored and remnant grasslands. A higher number of species, and thus an increased seed diversity in the vegetation in grazed grasslands, means more seeds which can potentially contribute to the seed bank, as long as grazing is not overly intensive so seed may set, and the disturbance and trampling activity of livestock may help these seeds to get integrated into the soil through gaps created on the surface (Jacquemyn et al, 2011; Klaus et al, 2018). Hence, long‐term regular grazing may help create a positive feedback loop through which species are more able to establish initially in gaps created (either via spatial dispersal or from the soil seed bank) and are subsequently more able to regenerate from a more diverse seed bank.…”
Section: Discussionmentioning
confidence: 99%
“…Grubbing, trampling or wallowing creates vital microsites in which dispersed seeds can germinate and possibly establish (Eriksson and Ehrlén, 1992; Pakeman and Small, 2005). These activities can also help seeds to integrate into the soil and to build up a persistent seed bank (Faust et al, 2011; Klaus et al, 2018). Grazing therefore leads to higher species diversity in both the vegetation and the seed bank communities, which enhances the resilience of grasslands.…”
Section: Introductionmentioning
confidence: 99%